New insights into thyroglobulin gene: Molecular analysis of seven novel mutations associated with goiter and hypothyroidism - Citterio, Cintia Eliana (2013)
The thyroglobulin (TG) gene is organized in 48 exons, spanning over 270 kb on human chromosome 8q24. Up to now, 62 inactivating mutations in the TG gene have been identified in patients with congenital goiter and endemic or non-endemic simple goiter. The purpose of the present study was to identify and characterize new mutations in the TG gene. We report 13 patients from seven unrelated families with goiter, hypothyroidism and low levels of serum TG. All patients underwent clinical, biochemical and imaging evaluation. Single-strand conformation polymorphism (SSCP) analysis, endonuclease restriction analysis, sequencing of DNA, genotyping, population screening, and bioinformatics studies were performed. Molecular analyses revealed seven novel inactivating TG mutations: c.378C>A [p.Y107X], c.2359C>T [p.R768X], c.2736delG [p.R893fsX946], c.3842G>A [p.C1262Y], c.5466delA [p.K1803fsX1833], c.6000C>G [p.C1981W] and c.6605C>G [p.P2183R] and three previously reported mutations: c.886C>T [p.R277X], c.6701C>A [p.A2215D] and c.7006C>T [p.R2317X]. Six patients from two families were homozygous for p.R277X mutation, four were compound heterozygous mutations (p.Y107X/p.C1262Y, p.R893fsX946/p.A2215D, p.K1803fsX1832/p.R2317X), one carried three identified mutations (p.R277X/p.C1981W-p.P2183R) together with a hypothetical micro deletion and the remaining two siblings from another family with typical phenotype had a single p.R768X mutated allele. In conclusion, our results confirm the genetic heterogeneity of TG defects and the pathophysiological importance of altered TG folding as a consequency of truncated TG proteins and missense mutations located in ACHE-like domain or that replace cysteine.